250 AUDIT INTO THE USE AND COMPLICATIONS OF MAINTENANCE INHALER THERAPY IN MEDICALLY ADMITTED PATIENTS OVER THE AGE OF 65 YEARS. (25th October 2022) - Walsh, S; Mulroy, M
Abstract: Background: Adequate maintenance inhaler use is associated with improved symptom control and reduced exacerbation rates, however, cognitive impairment and limitations in dexterity can be a barrier to inhaled therapy. Methods: Between the 20th of April and 30th May 2022 patients admitted to our ward over the age of 65 years had their maintenance inhaler technique assessed using the National Asthma Council of Australia checklist. Symptom control was assessed by either the Asthma Control Test (ACT) or the Chronic Obstructive Pulmonary Disease (COPD) assessment tool (CAT). The 4 AT score was used to screen for neurocognitive impairment. Results: 20 patients were recruited to the study. 40% were male. Mean age 81.5 years +- 6.8years. The respiratory diagnosis was COPD in 70%, Asthma 20%, Interstitial Lung Disease 5% and bronchiectasis 5%. 65 % had pulmonary function testing performed. Asthma symptom control was within target in 75% of the asthma patients (ACT score >20). Mean score 21 +- 2.5. COPD symptom control was within target in 31% of patients (CAT score <10) . Mean CAT score of 19.3 +- 8. 4. 20% had a pre-admission diagnosis of neurocognitive impairment. The mean 4AT score of the cohort was 1.2. 35% had audible wheeze at the time of review. 80% of inhalers were prescribed for the licensed indication. 35% had potential complications of inhaler therapy – 25% pneumonia and 10% oral candidiasis. Notably all pneumonias were associated with fluticasone. Inhaler technique was associated with errors in almost a quarter of all patients (24%). Increasing 4AT score correlated with high likelihood of inhaler errors, R = 0.63. Conclusion: Poor inhaler technique is correlated with neurocognitive impairment. Pneumonia is a potential complication of inhaler therapy and represents an opportunity for deprescribing in patients with COPD.